Systemic cycles of accumulation, spatial expansion and chaos: Adding a missing link - Giorgos Galanis Goldsmiths; Christian Koutny; Isabella Weber (University of Massachusetts, Department of Economics, 2022)
We re-examine the Systemic Cycles of Accumulation (SCA) of Arrighi (2010) and Arrighi and Silver (1999) which provide a framework for the analysis of the cyclical patterns of geographical expansion of trade and production and the related shifts of hegemonic power within the world capitalist system. Within the SCA framework, the last stage of a hegemonic cycle is characterized by what is called 'systemic chaos', however the drivers of these chaotic dynamics have not been explicitly analyzed. This article fills this gap by providing a link between the accumulation process, the spatio-temporal fix, and systemic chaos, in three steps. First, we show that the accumulation process can be mathematically described by what is known as a logistic map. Second, we show that the different stages of the accumulation processes in Arrighi (2010) correspond to different values of the parameter of the logistic map which in our framework captures barriers to accumulation. Third, drawing on well-known properties of the logistic map in dynamic systems, we demonstrate that as this parameter crosses certain thresholds, the accumulation process becomes more complex exhibiting nontrivial and chaotic dynamics. In this way, our approach provides the missing detailed understanding of how systemic chaos is an outcome of the contradictory dynamics of capital accumulation itself while being based on the key insights of the SCA framework of hegemonic cycles.
Keywords: 330; systemic cycles of accumulation; hegemony; spatial fix; chaos; switching crisis